Development of Image Processing Based Methods Using Augmented Reality in Higher Education - Yaman, Orhan; Karakose, Mehmet (Ieee, 2016)
Today, computer-based training is developing rapidly. The visual education is also quite commonly used in higher education as well as in primary and secondary education. The tablets, smart boards and computers constitute the basis of visual education. Visual education has many advantages, such as learning faster, memorability and in terms of paper expenses. The visual animations and presentations have become a very important material in higher education in recent years along with the development of computer technologies. The image processing has been proposed to improve instructiveness in higher education courses in the fields of Medicine, Engineering and Science. In the field of medicine, the image processing methods can be used to show the diseased regions in an easier way in many images such as CT and MR images [5]. In the fields of engineering, image processing can be used to improve images in visual courses in the fields such as Geology, Civil Mining engineering. In addition, it can be easily preferred and applied in the departments such as Chemistry, Biology and Geography in the field of Science. The unclarity of images used in courses leads to ambiguity. In this study, image processing based approaches have been developed to ensure more effective learning of the courses in higher education. Image processing is a technology which is used in many places in daily life. The image processing methods have become widespread along with the acceleration of computer technologies. Today, image processing is used in many environments such as education, health, defense industry and industrial areas. Successful results are obtained application areas such as fault diagnosis and condition monitoring using image processing methods. Today, the augmented reality which is commonly used in the field of education can further increase its contribution to the field of education by associating with image processing methods.
15th International Conference on Information Technology Based Higher Education and Training (ITHET) -- SEP 08-10, 2016 -- Istanbul, TURKEY
Keywords: augmented reality; image processing; higher education